Effects of Antenatal Betamethasone on Maternal and Fetoplacental Matrix Metalloproteinases 2 and 9 Activities in Human Singleton Pregnancies. (1st July 2006) - Gharraee, Zahra; Beharry, Kay D.A.; Valencia, Arwin M.; Cho, Steve; Guajardo, Leonel; Nageotte, Michael P.; Modanlou, Houchang D.
Abstract : Background: A single course of antenatal betamethasone is administered to women at risk of preterm labor to advance fetal lung maturation. Matrix metalloproteinases (MMPs) are collagen-degrading enzymes that remodel extracellular matrix components during lung development. We tested the hypothesis that the effects of betamethasone on fetal lung maturation involve changes in MMP activity. Methods: We conducted a prospective, observational pilot study of three groups of singleton pregnancies. Group 1 ( n = 21) was composed of women who were antenatally treated with a single course of betamethasone and who delivered < 37 weeks of gestation, group 2 ( n = 7) was composed of matched untreated women who delivered < 37 weeks of gestation, and group 3 ( n = 15) was composed of untreated women who delivered > 37 weeks of gestation. Maternal blood, mixed cord blood, and placental samples were collected at the time of delivery for MMP-2 and MMP-9 activity and tissue inhibitor of metalloproteinases (TIMP)-1 and -2 levels. Results: MMP-2 activity was significantly higher in the maternal, placental, and fetal compartments in group 1 compared with group 2 ( p < .05). TIMP-2 levels were lower in groups 1 and 2 compared with group 3. Maternal TIMP-2 levels were higher ( p < 0.003), whereas fetal TIMP-1 ( p < .01) and MMP-9 to TIMP-1 ratios ( p < .05) were lower when delivery was delayed more than 2 weeks following betamethasone treatment. Conclusion: We conclude that elevated MMP-2 activity in the maternal and fetoplacental compartments may suggest a mechanism, in part, for betamethasone-induced fetal lung maturation.